The Role of the Principal in Implementing the Teaching Factory Program to Improve Students’ Competence at Krian 2 Sidoarjo Center of Excellence Vocational High School - Mochammad Ja'far Sodiq; Muhamad Sholeh (Sustainable Human Capital Development Journal, 2025)
This study aims to describe in depth the role of the principal in implementing the Teaching Factory (TeFa) program to improve students’ competence at the Center of Excellence Vocational High School Krian 2 Sidoarjo. The research employed a qualitative descriptive approach with data collected through interviews, observations, and document studies. Data analysis was conducted through the stages of data condensation, presentation, and conclusion drawing, with the validity tested using source triangulation, technique triangulation, and member checking. The findings show that the principal’s role encompasses three main dimensions: 1) As a manager, the principal plays an active role in planning, implementing, and evaluating the TeFa program by establishing collaboration strategies with business and industry partners, synchronizing the curriculum and facilities, and developing human resources. 2) As a leader, the principal fosters participatory collaboration with teachers, students, and industry partners through open communication, continuous coaching, and cross-sector empowerment. 3) As an innovator, the principal encourages creativity among teachers and students by providing financial support, facilities, and flagship programs such as Krian 2 Vocational High School, Sidoarjo Ready to Work, while integrating enterprise-based learning that serves real customers as a means of competence evaluation. Thus, the principal’s adaptive and visionary role has proven to enhance students’ hard skills and soft skills, enabling them to be more prepared for the workforce, further education, and independent entrepreneurship.